Provision for storage of scheduled waste in electronic factory / Tun Afza Abdul Manap - Abdul Manap, Tun Afza (2001)
Scheduled waste is a dangerous things and give affects to human been ,flora and fauna. Mostly, many scheduled waste generated by the factories. All parties must involved and take consideration about scheduled waste management in the factory. Storage of scheduled waste in the factory is important work to be done. Generally , a few waste generator do not implement with the procedures and regulation given by the government for scheduled waste storage in factory. A few waste generator just think about profit from production from factory. The waste generator must think the best way how to manage their money for the disposal of scheduled waste. The best way to reduce cost for disposal of scheduled waste is buying a machine to reduce weight of the scheduled waste or recycle any scheduled waste to used back in the factory. Government must changed any regulation under legislation and give further information how to manage the scheduled waste properly in the factory.